The Great Men of the Great War: Heroic Martial Masculinity in the Wartime Works of Harvey Dunn - Magnusen, Kaia L. (Hungarian Journal of English and American Studies, 2022)
American artist Harvey Dunn was one of the eight soldier artists recruited by the American Expeditionary Forces (A.E.F) during World War I (1914-1918). His wartime works can be situated within the moralizing, Wilsonian rhetoric surrounding America’s entry into the war and linked with a conception of masculinity that was inextricably connected with war service. These images of heroic, martial, American masculinity align with the pronouncements President Woodrow Wilson made to justify America’s participation in the war. They reflect the gendered language and imagery American propaganda posters used to glorify enlisted soldiers as masculine heroes. Rather than portraying German soldiers as savages, Dunn altered this discourse by portraying cowardly German soldiers in moments of vulnerability. Dunn’s wartime images emphasize American ideas of martial masculinity in order to convey patriotic and propagandistic notions concerning the righteousness of the Allied cause, the superiority of American manhood, and the might of the American military. (KLM)